PERTIMBANGAN HAKIM PADA PENJATUHAN HUKUMAN KEPADA PELAKU TINDAK PIDANA PENGANIAYAAN KEPADA ANAK YANG MENGAKIBATKAN MATI - Ndruru, Novari (LPPM Universitas Nias Raya, 2024)
An act that violates the law, has an element of error, and is punishable by a crime is called a criminal act. The aim of criminal punishment against the perpetrator is to guarantee public interests and maintain legal justice. Decision number 29/Pid.Sus/2017/PN.Kpg is one of the criminal acts of obscenity that has been sent and tried by the Kupang District Court. For alleged violations of Article 80 paragraphs (3) and (4) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, the perpetrator was sentenced to 4 (four) years in prison. Normative legal research using a statutory regulation approach, case approach, comparative approach and analytical approach is the type of research carried out. Secondary data obtained from library sources, including primary and secondary law books, was used to collect data. An inductive approach was used to obtain conclusions from qualitative descriptive data analysis. From the results of the research and discussion, it can be determined that anyone who commits a criminal act against Decision Number 29/Pid.Sus/2017/PN.Kpg) will be punished in accordance with the applicable provisions. The provisions in paragraphs (1), (2), and (3) are added if necessary, and if it results in death, imprisonment is based on Article 80 paragraphs (3) and (4) of Law Number 35 of 2014 concerning Child Protection up to 15 year. It was his parents that he felt for. The perpetrator was sentenced to four years in prison by the panel of judges. Based on the applicable provisions, the judge imposed sanctions. The author suggests that judges in the panel that examines and decides on a criminal case should be more careful in deciding whether the actions carried out are in accordance with the provisions of the relevant laws and regulations.